A clinical study of neonatal dermatosis - Shah, Shazia; Yaseen, Ummer; Gupta, Sanjay (International Journal of Contemporary Pediatrics, 2017)
Background: The neonatal period is the first 4 weeks of extra-uterine life. Neonatal dermatology encompasses a spectrum of cutaneous disorders from benign to life threatening. The present study was undertaken to evaluate the various dermatoses and hence assess the spectrum of dermatological conditions during the neonatal period and to study the relationship of neonatal dermatoses with maturity and birth weight of the neonates. Methods: Three hundred neonates with cutaneous manifestations, attending the OPD of dermatology and Paediatrics during one year period, were studied. Neonates receiving phototherapy and those with lesions secondary to trauma were excluded. Clinical history coupled with complete general physical, systemic and dermatological examination. Results: Three hundred cases of neonatal dermatoses were included in study. Out of 300 cases, 179 (59.7%) were male babies and 121 (140.3%) were female (sex ratio 1:5), 271 (70.3%) were term babies, 27 (9%) were preterm and 2 (0.7%) were post term. Transient/non-infective cutaneous lesions were the commonest 144 (48%) followed by Infectious 68 (22.67%), eczematous disorder 33 (11%) and pigmentary dermatoses 25 (8.33). Vascular lesions and hematomas accounted for 18 (6%) while genodermatoses were seen 7 (2.33%). 5 cases of subcutaneous fat disorders were observed. Conclusions: As the spectrum of neonatal dermatology is vast, its knowledge to dermatologist is very important so as to differentiate the more common benign disorders from less frequent life-threatening dermatoses, so that timely intervention could facilitate a better therapeutic outcome.